Constraining the fast radio burst properties using the joint distributions of dispersion measure and fluence of the events detected at Parkes, ASKAP, CHIME, and UTMOST. Issue 1 (15th January 2021) - Bhattacharyya, Siddhartha; Bharadwaj, Somnath
ABSTRACT: The Parkes, ASKAP, CHIME, and UTMOST telescopes, which have all detected fast radio bursts (FRBs), each works at a different frequency and has a different detection criteria. Using simulations, we have combined the constraints from all four telescopes to identify an allowed range of model parameters (α, E_33) for the FRB source population. Here, α is the spectral index and E_33 is the mean FRB energy in units of 10^33 J across a 2128–2848 MHz band in the FRB rest frame. We have considered several different FRB energy distributions, and also different scenarios for the scattering pulse broadening, the event rate density variation with z and the host dispersion measure (DM). We find that in all cases, the common allowed region includes the range −3.9 ≤ α ≤ −1.3 and 0.42E_331 . In all case, large values α > 4 and E_33 60 are ruled out. Considering the allowed (α, E_33) parameter range, we predict that CHIME is unlikely to detect an FRB with extragalactic dispersion measure (DMEx ) exceeding 3700 pc cm^-3 . A substantially larger DMEx in the large FRB sample anticipated from CHIME would falsify the assumptions of the present analysis. Our analysis is expected to yield tighter parameter constraints with the advent of more FRB data.